2009
DOI: 10.14710/jitaa.34.3.153-158
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Patterns of Carcass Tissues Within Wholesale Cuts in Fattening Steer

Abstract: An investigation was conducted on beef carcasses, aimed at identifying the growth patterns of wholesale cuts and their tissues in steer during fattening phase. This study involved 69 grass-fed steers with a liveweight range of 300 to 600 kg. They had entered, or were progressing along, their fat deposition phase. An allometric model (Huxley, 1932) was used to study the growth patterns of carcass tissues within wholesale cuts. In general, The growths of muscle and fat within wholesale cuts followed similar patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
7
1
2
Order By: Relevance
“…During the fattening phase, the growth impetus of fat was predominantly high relative to that of muscle and bone (Priyanto et al, 2009). This made the former tissue having an important role in determining compositional changes of a carcass and consequently the yield of beef (Mukai et al, 2004;Vieira et al, 2006).…”
Section: �Ntroduct�onmentioning
confidence: 99%
See 2 more Smart Citations
“…During the fattening phase, the growth impetus of fat was predominantly high relative to that of muscle and bone (Priyanto et al, 2009). This made the former tissue having an important role in determining compositional changes of a carcass and consequently the yield of beef (Mukai et al, 2004;Vieira et al, 2006).…”
Section: �Ntroduct�onmentioning
confidence: 99%
“…The changes in carcass composition after the onset of fattening phase are largely attributable to the increasing proportion of fat in a carcass. Advancing in carcass fatness would be followed by increasing carcass fat but decreasing carcass muscle percentages due to the much higher growth impetus of carcass fat relative muscle and bone (Priyanto Priyanto et al, 2009). Consequently, increasing carcass fatness .…”
Section: �Ntroduct�onmentioning
confidence: 99%
See 1 more Smart Citation
“…Saleable beef yield and its distribution within carcass have been intensively studied (Priyanto et al, 1999;Mukai et al, 2004;Hafi d & Priyanto, 2006, Vieira et al, 2006Priyanto et al, 2009). At lower fatness, it was reported that ca le with larger frame size had be er yield percentages of saleable beef, if compared to that with smaller frame size (Priyanto et al, 1999;Bidner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At lower fatness, it was reported that ca le with larger frame size had be er yield percentages of saleable beef, if compared to that with smaller frame size (Priyanto et al, 1999;Bidner et al, 2009). Such variations in beef yield were associated primarily with maturity type diff erences because of the diff erential growth pa erns of their carcass tissues (Priyanto et al, 1999;Priyanto et al, 2009). It is the carcass' muscle contributing predominantly to the yield of saleable beef.…”
Section: Introductionmentioning
confidence: 99%